P188 The NEWS score as a surrogate marker for pH during NIV. (12th November 2019) - Aziz, S; Robbins, A; Tweed, C; Gittens, J
Abstract : Introduction and objectives: The BTS recommends arterial blood gas (ABG) sampling prior to initiation of non-invasive ventilation (NIV) for Type 2 Respiratory Failure (T2RF) and after 1-hour to guide treatment. 1 We hypothesised that the National Early Warning Score (NEWS 2) score could be a surrogate marker for arterial pH, and therefore be used to help guide management in patients started acutely on NIV. Methods: A retrospective analysis was conducted on patients started on acute NIV due to hypercapnic respiratory failure between 05/12/2018 and 12/072019. Patient notes and electronic records were used to collect ABG results and timings, and NEWS 2 scores. The correlation between the recorded pH and NEWS scores at each time point was tested using Spearman's rank correlation coefficient. Results: Only 35/101 of patients (35%) started on acute NIV had both a pre-initiation and 1-hour ABG. There were 19/35 patients (54%) with adequate data available in their notes for inclusion. No significant correlation was found between pre-NIV initiation NEWS 2 score and arterial pH ( rs =-0.35, p=0.13). A significant negative correlation was found between NEWS 2 score and arterial pH at 1-hour after initiation of NIV ( rs =-0.55, p=0.01*). No significant correlation was found between a change in NEWS 2 score and change in arterial pH between pre-NIV initiation and 1-hour of NIV ( rs =-0.43, p=0.06). Conclusions: We did not detect a statistically significant correlation between a change in NEWS 2 score and arterial pH in the first hour NIV therapy for acidotic T2RF. These findings do not support the use of the NEWS 2 score in isolation to monitor patients on NIV. However, we also found that a large proportion of patients were not adequately monitored using ABG sampling. To ensure optimum management of patients receiving NIV, ABG sampling must be prioritised and systems put in place to facilitate these tests. References: Davidson AC, Banham S, Elliott M, et al . BTS/ICS guideline for the ventilatory management of acute hypercapnic respiratory failure in adults Thorax 2016;71:ii1-ii35.